2010
DOI: 10.1042/cs20090537
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma concentrations of anterior gradient 2 protein are positively associated with ovarian cancer

Abstract: Ovarian cancer is often asymptomatic and is diagnosed at an advanced stage with poor survival rates, thus there is an urgent need to develop biomarkers for earlier detection of ovarian cancer. In the present study, we demonstrate for the first time that the previously reported metastasis-inducing protein AGR2 (anterior gradient protein 2) can be detected in the blood of ovarian cancer patients. Using a newly developed ELISA, we show significantly increased concentrations of AGR2 protein in plasma from cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
(29 reference statements)
3
27
0
Order By: Relevance
“…Agr2 has been shown to bind mucin proteins directly and by managing their conformation as they traffick through the endoplasmic reticulum (ER), Agr2 might increase their stability and expression (Zhao et al, 2010;Higa et al, 2011;Niederreiter and Kaser, 2011). Expression of Agr2 is also induced by ER stress and is highly enhanced in multiple carcinomas, leading to stimulation of proliferation (Liu et al, 2005;Zweitzig et al, 2007;Ramachandran et al, 2008;Barraclough et al, 2009;Edgell et al, 2010;Maresh et al, 2010;Bu et al, 2011). More relevant in light of our results are previous findings showing that Agr2 can alter cell fates by inducing ectopic cement gland differentiation and anterior neural fate in Xenopus laevis (Aberger et al, 1998).…”
Section: Discussionsupporting
confidence: 55%
“…Agr2 has been shown to bind mucin proteins directly and by managing their conformation as they traffick through the endoplasmic reticulum (ER), Agr2 might increase their stability and expression (Zhao et al, 2010;Higa et al, 2011;Niederreiter and Kaser, 2011). Expression of Agr2 is also induced by ER stress and is highly enhanced in multiple carcinomas, leading to stimulation of proliferation (Liu et al, 2005;Zweitzig et al, 2007;Ramachandran et al, 2008;Barraclough et al, 2009;Edgell et al, 2010;Maresh et al, 2010;Bu et al, 2011). More relevant in light of our results are previous findings showing that Agr2 can alter cell fates by inducing ectopic cement gland differentiation and anterior neural fate in Xenopus laevis (Aberger et al, 1998).…”
Section: Discussionsupporting
confidence: 55%
“…In the clinical setting, AGR2 protein expression in the primary tumor is an independent prognostic indicator of poor outcome in patients with breast [29] and prostate adenocarcinomas [30], and one recent study showed that increased AGR2 protein in plasma is associated with ovarian cancer [31]. …”
Section: Resultsmentioning
confidence: 99%
“…79 AGR2 is a secreted, cancer-associated protein and upregulated in many types of epithelial cancer, 10,11 including breast, 12,13 lung, 14,15 colon, 16 ovarian, 17,18 esophageal, 19 and pancreatic 20,21 beside prostate. Compared with non-cancer, AGR2 is highly expressed in prostate cancer at both the mRNA and protein levels.…”
Section: Introductionmentioning
confidence: 99%